A Study on the Religious Percept of Removing Goods from the Place of Safe Custody while under Hypnosis - ????? ???, ??? ????; ???? ????, ??? ?????; ??????, ???? (???????? ??????? ?????? ????)
A requirement of Hadd theft on which there is consensus, in addition to the requirement that the stolen goods are kept in a place of safe custody, is that the thief, alone or with another?s participation, removes the goods from the place of safe custody. One of the most important doubtful instances of removing the goods is theft while under hypnosis. The authors, after analyzing the criterion of removing the goods from the place of safe custody, have concluded that, in certain instances, it applies to the hypnotist's act, i.e. where they have the capacity that the act of removing the goods from the place of safe custody is attributed to them and their act is an example of contributory removal. In some other instances, the Hadd of imputation is executed against the hypnotized person i.e. where they have the capacity that the act of removing the good from the place of safe custody is attributed to them. If there is doubt whether removal from the place of safe custody has taken place, although there is dubiety concerning concept and over the least and the most of one thing, given Mohammad Ibn Muslim's  sahiha (authentic) tradition,  the requirements of removing the good from the place of safe custody, as well as the requirement that the goods are kept in a place of safe custody, are included in the concept of theft and accordingly, the theft verse loses its generality and may not be invoked. Therefore, in such case, due to astonishment and wander, by invoking the requirement of Dar rule (no Hadd is executed in case of dubiety), Hadd of imputation is not executed against the thief.